Enhancing taxpayers compliance by using Snap to Save (S2S) apps / Mohd Hafiz Bakar and Siti Norbaya Yahaya - Bakar, Mohd Hafiz; Yahaya, Siti Norbaya (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The Snap to Save (s2s) application was developed to assist and enable the taxpayers to keep, monitor and track their spending record for the purpose of income tax declaration every year. The taxpayers eligible for tax relief by declaring their purchase for previous year spending according to the relief items provided by Inland Revenue Board of Malaysia (LHDN). This can contribute to the tax compliance among the taxpayers. Accuracy and complexity of tax has a significant on tax compliance in Malaysia. The taxpayers can utilise this Snap to Save (s2s) tool to help them record their purchases for that specific year, including the date, items, amount, and receipts. The taxpayers need to keep the proof of purchase of that item for at least seven years and this application can assist them accordingly. The word "snap" refers to capture the receipts and will keep on their own drive. The word "SAVE" refer to the systematic way of recording their purchase, where every item that they declare to claim the tax relief is very valuable and it can save a lot of time and energy for the taxpayers in tracking their records efficiently. This app is very user friendly and easy to use. The development of Snap to Save (s2s) application is using the Google Appsheet where all the sections coordinate with the data we created in Google Sheets to the apps directly. It can be installed for Android and iOS user. After snap the receipt, user need to fill in their spending details on the entries column and it will appear in the summary of spending folder. All the data will store directly to the user drive, and they can track and manage it consequently either from their handphone or laptop. Thus, this app will assist in term of managing the taxpayers supporting document when doing their income tax declaration. Snap to Save (s2s) application can save a lot of time and energy of the taxpayers and it can contribute to systematic and efficient process during the declaration of income tax. The most important thing is this will encourage a tax compliance among the taxpayers in Malaysia.